Inhibition of tumour necrosis factor-alpha and interleukin 6 production by mononuclear cells following dietary fish-oil supplementation in healthy men and response to antioxidant co-supplementation. - Trebble, T; Arden, N; Stroud, M; Wootton, SA; Burdge, G; Miles, E; Ballinger, AB; Thompson, R; Calder, P (2003)
Increased dietary consumption of the n-3 polyunsaturated fatty acids (PUFA) eicosapentaenoic acid (20 : 5n-3; EPA) and docosahexaenoic acid (22 : 6n-6; DHA) is associated with their incorporation into circulating phospholipid and increased production of lipid peroxide metabolites. The relationship between peripheral blood mononuclear cell (PBMC) function, n-3 PUFA intake and antioxidant co-supplementation is poorly defined. We therefore investigated tumour necrosis factor (TNF)-alpha and interleukin (IL) 6 production by PBMC and phospholipid fatty acid composition in plasma and erythrocytes of healthy male subjects (n 16) receiving supplemental intakes of 0.3, 1.0 and 2.0 g EPA+DHA/d, as consecutive 4-week courses. All subjects were randomised in a double-blind manner to receive a concurrent antioxidant supplement (200 microg Se, 3 mg Mn, 30 mg D-alpha-tocopheryl succinate, 90 mg ascorbic acid, 450 microg vitamin A (beta-carotene and retinol)) or placebo. There was a positive dose-dependent relationship between dietary n-3 PUFA intake and EPA and DHA incorporation into plasma phosphatidylcholine and erythrocyte phosphatidylethanolamine, with a tendency towards a plateau at higher levels of intake. Production of TNF-alpha and IL-6 by PBMC decreased with increasing n-3 PUFA intake but tended towards a 'U-shaped' dose response. Both responses appeared to be augmented by antioxidant co-supplementation at intermediate supplementary n-3 PUFA intakes. Thus, increased dietary n-3 PUFA consumption resulted in defined but contrasting patterns of modulation of phospholipid fatty acid composition and PBMC function, which were further influenced by antioxidant intake.